Throughput Multiplexing Efficiency of MIMO Terminal Antennas Considering Adaptive MCS and Layers - Wei, Jianchuan; Huang, Xiaoyu; Qian, Bingyi; Zhang, Aofang; Wei, Kunpeng; Chen, Xiaoming (IEEE International Workshop on Electromagnetics (Online), 2023)
The throughput performance of the multipleinput multiple-output (MIMO) system is often affected by antenna imperfections (power imbalance and correlation), especially at the mobile station side. In this paper, the original throughput model is extended so that it can be used in systems that adaptively change the modulation and coding scheme (MCS) and data streams (layers) according to the channel quality. In addition, the derived throughput multiplexing efficiency (ME) in previous work is only applicable to performance evaluation at peak throughput with fixed MCS and number of layers. A mean ME (MME) is proposed in this work, which can characterize the overall effect of throughput degradation due to imperfect MIMO terminal antennas under any channel quality. The correlation-based channel model is adopted to verify the rationality of MME. It is shown that the throughput-based MME is closer to the theoretical value of capacity-based ME for in an adaptive MIMO system.